APM:agent protection mechanism applied for IaaS platform - Peiru FAN; Bo ZHAO; Mingtao NI; Zhihong CHEN (Tongxin xuebao)
The interference of false or fake test data on IaaS platform will contaminate the evaluation results,confusing users’ choices for IaaS services.To solve this problem,an agent protection mechanism (APM) for IaaS platform test environment was proposed.It ensured the integrity and commanded validity of the agent without additional hardware or software.Also an effectiveness verification approach based on requests was presented to detect APM failure problems timely.An experiment environment according to APM was implemented to evaluate the effectiveness and the performance overhead.Experimental results show that the APM is effective in protecting agent integrity and command validation,and its performance overhead is minor.